Oridonin inhibits inflammation of epithelial cells via dual-targeting of CD31 Keap1 to ameliorate acute lung injury - Zhao, Yue; Jin, Hua; Lei, Kawai; Bai, Li-Ping; Pan, Hudan; Wang, Caiyan; Zhu, Xiaoming; Tang, Yanqing; Guo, Zhengyang; Cai, Jiye; Li, Ting (Frontiers in Immunology, 2023)
Acute lung injury and acute respiratory distress syndrome are the leading causes of COVID-19 mortality. However, few drugs can effectively treat ALI/ARDS because endothelial cells form barriers that impede drug delivery to lung tissues. Therefore, a prompt and aggressive treatment strategy is necessary. Here, we developed a formulation consisting of anti-CD31 monoclonal antibody-conjugated oridonin nanoparticles (anti-CD31-ORI-NPs) to intensively attenuate ALI/ARDS. The results demonstrated that anti-CD31-ORI-NPs could penetrate endothelial cell barriers and specifically accumulate in lung tissues rather than other organs. Accordingly, anti-CD31-ORI-NPs improved the efficacy to ameliorate acute lung injury in an animal model three times compared with free oridonin. Importantly, anti-CD31-ORI-NPs significantly decreased the cytotoxicity of endothelial cells at least two times that of free oridonin. Collectively, this delivery system overcomes the barrier to specifically carry more oridonin to the endothelial cells of lung tissues with low toxicity to alleviate inflammation. Our study offered a novel therapeutic promising strategy by using approved drugs to treat acute lung injury with high efficacy and low toxicity.